POREWATER STOICHIOMETRY OF TERMINAL METABOLIC PRODUCTS, SULFATE, AND DISSOLVED ORGANIC CARBON AND NITROGEN IN ESTUARINE INTERTIDAL CREEK-BANK SEDIMENTS - Weston N.B.; Porubsky W.P.; Samarkin V.A.; Erickson M.; Macavoy S.E.; Joye S.B. (My University, 2006)
Porewater equilibration samplers were used to obtain porewater inventories of inorganic nutrients (NH 4 + , NO x , PO 4 3− ), dissolved organic carbon (DOC) and nitrogen (DON), sulfate (SO 4 2− ), dissolved inorganic carbon (DIC), hydrogen sulfide (H2S), chloride (Cl−), methane (CH4) and reduced iron (Fe2+) in intertidal creek-bank sediments at eight sites in three estuarine systems over a range of salinities and seasons. Sulfate reduction (SR) rates and sediment particulate organic carbon (POC) and nitrogen (PON) were also determined at several of the sites. Four sites in the Okatee River estuary in South Carolina, two sites on Sapelo Island, Georgia and one site in White Oak Creek, Georgia appeared to be relatively pristine. The eighth site in Umbrella Creek, Georgia was directly adjacent to a small residential development employing septic systems to handle household waste. The large data set (>700 porewater profiles) offers an opportunity to assess system-scale patterns of porewater biogeochemical dynamics with an emphasis on DOC and DON distributions. SO 4 2− depletion (SO 4 2− )Dep was used as a proxy for SR, and (SO 4 2− )Dep patterns agreed with measured (35S) patterns of SR. There were significant system-scale correlations between the inorganic products of terminal metabolism (DIC, NH 4 + and PO 4 3− ) and (SO 4 2− )Dep, and SR appeared to be the dominant terminal carbon oxidation pathway in these sediments. Porewater inventories of DIC and (SO 4 2− )Dep indicate a 2:1 stoichiometry across sites, and the C:N ratio of the organic matter undergoing mineralization was between 7.5 and 10. The data suggest that septic-derived dissolved organic matter with a C:N ratio below 6 fueled microbial metabolism and SR at a site with development in the upland. Seasonality was observed in the porewater inventories, but temperature alone did not adequately describe the patterns of (SO 4 2− )Dep, terminal metabolic products (DIC, NH 4 + , PO 4 3− ), DOC and DON, and SR observed in this study. It appears that production and consumption of labile DOC are tightly coupled in these sediments, and that bulk DOC is likely a recalcitrant pool. Preferential hydrolysis of PON relative to POC when overall organic matter mineralization rates were high appears to drive the observed patterns in POC:PON, DOC:DON and DIC:DIN ratios. These data, along with the weak seasonal patterns of SR and organic and inorganic porewater inventories, suggest that the rate of hydrolysis limits organic matter mineralization in these intertidal creek-bank sediments.
Keywords: CARBON; DISSOLVED ORGANIC CARBON (DOC); DISSOLVED ORGANIC NITROGEN (DON); SEDIMENT METABOLISM; NITROGEN; SULFATE REDUCTION